2018
DOI: 10.1525/mp.2018.35.4.502
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological Responses to “Happy” and “Sad” Music

Abstract: Lundqvist, Carlsson, Hilmersson, and Juslin (2009) presented evidence of differential autonomic emotional responses to “happy” and “sad” music in healthy adult listeners. The present study sought to replicate and extend these findings by employing a similar research design and measurement instruments. Therefore, we used instrumental film music instead of vocal music, and assessed listeners’ music expertise. The present results show similarities and differences in patterns of psychological and physiological res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 0 publications
5
23
0
3
Order By: Relevance
“…Unlike speech or noise, music has a remarkable function of evoking and affecting listeners’ emotions 19 , 20 . Background music provides a unique window into how the brain works when music and cognitive tasks are presented simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike speech or noise, music has a remarkable function of evoking and affecting listeners’ emotions 19 , 20 . Background music provides a unique window into how the brain works when music and cognitive tasks are presented simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Al mismo tiempo, la percepción produce otras reacciones corporales y emocionales dependientes de los sistemas nerviosos autónomo y somático. Estas últimas se traducen en modulaciones de las frecuencias cardíaca y respiratoria, la presión arterial, la oxigenación de la sangre, la temperatura, la respuesta galvánica de la piel, el reflejo pupilar y múltiples actividades musculares como puede ser la cigomática (ejemplos en: Bullack, Büdenbender, Roden & Kreutz, 2018;Grewe, Nagel, Kopiez & Altenmüller, 2007;Hodges, 2010;Iwanaga & Moroki, 1999;Khalfa, Peretz, Blondin & Robert, 2002;Krumhansl, 1997;Lundqvist, Carlsson, Hilmersson & Juslin, 2009;Merrill, Omigie & Wald-Fuhrmann, 2020;Nyklíček, Thayer & Van Doornen, 1997;Orini et al, 2010). En el histórico de investigaciones que han estudiado las respuestas fisiológicas vinculadas a la música, las primeras hipótesis cuestionaron si la modificación de distintos parámetros musicales, tales como el tempo o la intensidad, supondría también de forma análoga una variación en las respuestas cardiovasculares y respiratorias.…”
Section: La Percepción Musical Y Su Influenciaunclassified
“…De igual manera, ha sido recurrente analizar cómo fragmentos musicales con gran número de disonancias o, por el contrario, mayoritariamente consonantes, actuarían en este sentido. Además, también se ha estudiado si las piezas musicales categorizadas por los participantes como "preferidas", o definidas subjetivamente como "tristes"/"alegres" o "excitantes"/"tranquilizantes", pueden influir sobre estas medidas biológicas y cómo lo hacen (Bullack et al, 2018;Iwanaga & Moroki, 1999).…”
Section: La Percepción Musical Y Su Influenciaunclassified
“…Reviews on these relationships have shown diverse results between studies, dependent on tasks, instructions, and music material used (for an overview see [ 20 22 ]). Also, the replication of single studies revealed similarities but also differences [ 23 ]. Studies using psychophysiological measures have investigated music-evoked emotions mainly by asking participants to report on discrete emotions or on affective dimensions (e.g., [ 24 28 ]).…”
Section: Introductionmentioning
confidence: 99%